Inhibition of deoxyribonucleic acid gyrase: effects on nucleic acid synthesis and cell division in Escherichia coli K-12. - Fairweather, N F (1980)
Mutants of Escherichia coli resistant to the antibiotic clorobiocin are also coumermycin resistant, and the mutation to resistance in at least one mutant was mapped near gyrB. We conclude, therefore, that clorobiocin inhibits deoxyribonucleic acid gyrase, and the drug was used to probe the role of this enzyme in vivo. Deozyribonucleic acid synthesis was preferentially inhibited but not completely blocked by the antibiotic. Transcription and cell division were also markedly affected. However, unlike other inhibitors of deoxyribonucleic acid synthesis, clorobiocin failed to induce the synthesis of protein X, the recA gene product. In mutants resistant to clorobiocin the replication velocity was unaffected, but initiation of deoxyribonucleic acid synthesis appeared to be delayed. We conclude that deoxyribonucleic acid gyrase, and hence the supercoiled structure of the chromosome, is important for transcription, normal initiation of deoxyribonucleic acid replication, and cell division. The possible role of deoxyribonucleic acid gyrase in the elongation of replication forks is also discussed.